(untitled) (Multidisciplinary Journal of Science and Technology, 2024)
In this article, we delve into the realm of advanced foreign experiments in statistical research to assess the effectiveness of the agrarian sector and explore avenues for their application at local levels. By examining innovative methodologies, empirical findings, and practical implications from international studies, our analysis aims to elucidate key insights, challenges, and opportunities in leveraging foreign research to enhance agricultural productivity, sustainability, and resilience in local contexts.